2020
DOI: 10.1029/2020jg005889
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Greenhouse Gases From Water Tracks Draining Arctic Hillslopes

Abstract: Experimental and ambient warming of Arctic tundra results in emissions of greenhouse gases to the atmosphere, contributing to a positive feedback to climate warming. Estimates of gas emissions from lakes and terrestrial tundra confirm the significance of aquatic fluxes in greenhouse gas budgets, whereas few estimates describe emissions from fluvial networks. We measured dissolved gas concentrations and estimated emissions of carbon dioxide (CO 2), methane (CH 4), and nitrous oxide (N 2 O) from water tracks, ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Our observations suggest that limited catchment dynamic storage in subarctic regions that are geologically similar to Pallas may have critical ecohydrological implications given future uncertainties in snowfall inputs (Bailey et al, 2021), and especially the timing of snowmelt processes. Simultaneously, ecohydrological connectivity strongly influences local and landscape processes in terms of carbon (DOC and DIC) export and GHG emissions (Harms et al, 2020). The latest sensor technologies and high‐frequency measurements can reveal highly‐detailed processes as shown by our snap‐shot analysis.…”
Section: Ways Forward In Subarctic Ecohydrologymentioning
confidence: 99%
“…Our observations suggest that limited catchment dynamic storage in subarctic regions that are geologically similar to Pallas may have critical ecohydrological implications given future uncertainties in snowfall inputs (Bailey et al, 2021), and especially the timing of snowmelt processes. Simultaneously, ecohydrological connectivity strongly influences local and landscape processes in terms of carbon (DOC and DIC) export and GHG emissions (Harms et al, 2020). The latest sensor technologies and high‐frequency measurements can reveal highly‐detailed processes as shown by our snap‐shot analysis.…”
Section: Ways Forward In Subarctic Ecohydrologymentioning
confidence: 99%
“…Simultaneously, environmental selection affects the composition (i.e. absolute makeup and relative diversity of taxonomy) of a bacterioplankton community and its functional ability to affect the local biogeochemistry, such as the decomposition of biological material, delivery of nutrients and DOC to surface waters, and generation of greenhouse gases (Harms et al, 2020; Malard & Pearce, 2018; Monteaux et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…During the Arctic melt season (May to June), the surface hydrologic connectivity between the land and rivers is enhanced. As the seasonal progression takes place, deeper water-saturated soil layers are thawed, and substances, microorganisms, and gases, like CH4, are mobilized through the lateral transfer from groundwater discharge into Arctic inland waters, particularly to the 635 fluvial network (Connolly et al, 2020;Harms et al, 2020;Saunois et al, 2020). It has been demonstrated that the majority of the CH4 emitted to the atmosphere from subarctic ponds is sustained by the discharge of CH4 from groundwaters upon the active layer thaw (Olid et al, 2021).…”
Section: Temporal Variability Of Methane In Kolyma Rivermentioning
confidence: 99%
“…The Arctic Ocean is one of the most river-influenced and land-locked of all the world oceans (Charkin et al, 2017;Shakirov et al, 2020), receiving annually about 10 % of the global runoff (Lammers et al, 2001), through the input from the main six Arctic rivers: Yenisey, Lena, Ob, Mackenzie, Yukon, and Kolyma. These rivers connect the ocean with the land, by mediating the transport of CH4 stored in terrestrial surface waters or groundwaters, or through 65 soil-water interactions in thawed water tracks (Connolly et al, 2020;Dabrowski et al, 2020;Harms et al, 2020;Saunois et al, 2020). Thus, the riverine transport of soil-derived CH4 from permafrost may influence the CH4 concentrations in the Arctic shelf system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation